The Application of Rehabilitation Therapy Occupational Competency Evaluation Model in the Improvement of College Students’ Innovation and Entrepreneurship - Zhenghan Liang (Occupational Therapy International)
This paper constructs an evaluation model of occupational competency in rehabilitation therapy and applies it to the improvement of college students’ innovative and entrepreneurial competencies. Based on clarifying the connotation of college students’ entrepreneurial competency, this study carries out research on the evaluation system of college students’ entrepreneurial competency. First, the method of qualitative research is used to conduct in-depth interviews with college students and entrepreneurial mentors to understand the views of these groups on college students’ entrepreneurial competency, and the coding of the interview contents is carried out by applying the rooting theory, and finally, a theoretical model of the composition of college students’ entrepreneurial competency is derived. The front-line position of talent cultivation is the construction of faculty, because the faculty with high-quality vocational ability is an indispensable prerequisite for the development of universities, and the teaching level of the faculty is the key factor for the effectiveness of teaching to appear. Based on the perspective of role theory, we analyze the problems and reasons for the lack of competency in the role-playing process; integrate the three stages of understanding the role, playing the role, and adjusting the role with the competency model; and propose strategies to improve the competency of youth social workers in the process of playing the role, to help workers accurately understand the role, correctly play the role, and reasonably adjust the role. The curriculum is designed to cultivate the competency of college student nursing positions, which is conducive to improving the professional quality of college student nursing service providers and regulating college student nursing practice so that they can actively respond to problems. This will strengthen the entire teaching faculty and enhance the professional competence of full-time teachers.